Case Report: Transvaginal specimen extraction following totally laparoscopic D2 distal gastrectomy for gastric cancer in a patient with situs inversus totalis: with video - Li, Zeyu; Zhang, Xiaolong; Tian, Lifei; Liu, Zheng; Liao, Xinhua; Qiu, Jian; Wang, Guorong; Yan, Likun; Wang, Xiaoqiang; Wang, Xishan; Liu, Ruiting (Frontiers in Oncology, 2023)
ith its great advantages of fast post-operative recovery, natural orifice specimen extraction surgery (NOSES) has attracted increasingly attention worldwide. However, the NOSES in gastric cancer (GC) treatment still needs more clinical practice, especially for the rare anatomical anomaly. Situs inversus totalis (SIT) is a rare autosomal recessive anatomical anomaly with an incidence ranging between 1/8,000 and 1/25,000 births. We present a video of transvaginal specimen extraction following totally laparoscopic D2 distal gastrectomy performed in a 59-year-old female known to have SIT. Preoperative investigations revealed that the patient had early gastric cancer at the antrum. A gastroscopy report from the local hospital showed signet-ring cell carcinoma. The preoperative computed tomography scan revealed irregular thickening of the gastric wall at the junction of the greater curvature and antrum without metastasis to the lymph nodes. In total, laparoscopic D2 distal gastrectomy was performed with transvaginal specimen extraction. Billroth II with Braun anastomosis was performed for reconstruction. The length of the operation was 240 min without intraoperative complications and minimal blood loss of 50 ml. The patient was uneventfully discharged on postoperative Day 7. The final pathology confirmed signet-ring cell carcinoma confined to the mucosal muscle without metastasis in 16 lymph nodes. Transvaginal specimen extraction following totally laparoscopic D2 distal gastrectomy can be safely performed in patients with SIT and has similar surgical outcomes as usual laparoscopic gastrectomy.